Innovation in the Food Sector Through the Valorization of Food and Agro-Food by-Products 2021
DOI: 10.5772/intechopen.93997
|View full text |Cite
|
Sign up to set email alerts
|

Valorization Options of Strawberry Extrudate Agro-Waste. A Review

Abstract: This review summarizes and critically analyzes the different types of potential valorization options for strawberry extrudate in order to have a broader overview of the potential management of this waste. Animal feed is commonly used as a management option for the strawberry extrudate; however, most of the strawberry extrudate is disposed in landfills. Strawberry extrudate contains different bioactive compounds that encourage the use of an alternative management approach than landfilled. The present review off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 96 publications
(159 reference statements)
0
10
0
Order By: Relevance
“…Moreover, strawberry pulps are also rich in condensed tannins (up to 163 mg/100 g raw strawberry), which are also known as proanthocyanins, and the soluble phenolic content (SPC) of strawberry pomace was measured and found as 17 μg gallic acid equivalent/mg dw. In the same article, the SPC of black currant, red currant, blackberry, and raspberry was also discussed and reported as 50.44, 20.54, 46.50, and 36.72 μg GAE/mg dw, respectively. , …”
Section: Bioactive Compounds From Fruit Juice Processing Wastesmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, strawberry pulps are also rich in condensed tannins (up to 163 mg/100 g raw strawberry), which are also known as proanthocyanins, and the soluble phenolic content (SPC) of strawberry pomace was measured and found as 17 μg gallic acid equivalent/mg dw. In the same article, the SPC of black currant, red currant, blackberry, and raspberry was also discussed and reported as 50.44, 20.54, 46.50, and 36.72 μg GAE/mg dw, respectively. , …”
Section: Bioactive Compounds From Fruit Juice Processing Wastesmentioning
confidence: 97%
“…Generally, the residual part of this fruit is being used as animal feed. However, a considerable amount of berry wastes are still being disposed to the landfills and contribute to the greenhouse gas (GHG) emissions because of the high organic load . Therefore, it is important for any waste to be evaluated in terms of generating new possibilities for both protecting the agricultural soil quality and taking advantage of finding inexpensive sources of bioactive substances .…”
Section: Bioactive Compounds From Fruit Juice Processing Wastesmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the waste has little sale value and is therefore a net cost to the producers. Recently, the authors have suggested various streams for valorisation (adding value) to raspberries in terms of dried powders (Krivokapić et al ., 2021) and seeds (Daud et al ., 2022), strawberries into biochar, bioethanol and bioplastics (Cubero‐Cardoso et al ., 2020) which can reduce financial loss and wastage, but the high cost of producing these is questionable without scale.…”
Section: Introductionmentioning
confidence: 99%